Hematologic immune-related adverse events in skin cancer patients treated with immune checkpoint inhibitors: a case series - Falcone, Rosa; Frezzolini, Alessandra; Bruni, Emanuele; Verkhovskaia, Sofia; Carbone, Maria Luigia; Di Pietro, Francesca Romana; Chesi, Paolo; Piesco, Gabriele; Cantonetti, Maria; Marchetti, Paolo; De Galitiis, Federica; Failla, Cristina Maria (Frontiers in Pharmacology, 2026)
BackgroundImmune checkpoint inhibitors (ICIs) are the gold standard therapy for cutaneous melanoma and are also used effectively in treating other types of skin cancer. Hematologic toxicities are rare, but potentially a serious and life-threatening side effect of ICIs. Clinical and biological biomarkers able to predict these events have been poorly explored and have not yet been identified.Case presentationWe present four cases of hematologic toxicity in melanoma patients and one case in a patient with cutaneous squamous cell carcinoma, all of which arose during treatment with ICIs in an adjuvant or metastatic setting. Hemolytic anemia was the most frequent event; neutropenia with agranulocytosis happened in one case and was fatal. ICI treatment was discontinued in all five cases and was never restarted. Two prevalent features were male sex and older age (>70 years old). These events were independent of the response to ICIs. Indeed, they occurred in a patient who progressed during treatment and in patients who responded completely to therapy. Previous diarrhea due to ICIs (patients 1, 2, and 5), asthenia (patients 3 and 4), and a sudden increase in lactate dehydrogenase levels despite the absence of disease progression (patients 2, 3, 4, and 5) might be warning signs of subsequent hematologic irAEs.ConclusionOur study underscores the rarity and potential severity of hematologic toxicities, underlining the need for heightened clinician awareness and the incorporation of hematologic guidance into oncologic practice. Although predictive biomarkers remain unvalidated, monitoring immune cell subsets or recognizing warning signals early on may facilitate diagnosis and improve prognosis.